THERMODYNAMIC MODELING OF THE BALANCED PHASE CONTENTS OF THE CAST BORON-CONTAINING ALLOY - N. F. Nevar; Ju. N. Fasevich (Литьë и металлургия)
The program ASTRA-4 with thermodynamic database is used in this work fo r thermodynamic modeling of cast alloy, received due to volume alloying by boron. The modeling was carried out by means of several calculations with following specializing of parameters with binary and ternary diagrams of systems.